Effect of Production, Price, and Rupiah Exchange Rate on the Export Value of Cocoa Beans (HS 1801) in Indonesia - Sari, Sinta Dewi Kumala; Imaningsih, Niniek (Journal of Business Management and Economic Development, 2024)
Among Indonesia's many plantation exports, cocoa beans play a starring role. In general, the trends in the export value of cocoa beans is inseparable from external changes including prices, production, and exchange rates. The purpose of this study is to determine the effect of the independent variables cocoa bean price (X1), rupiah exchange rate (X2), and cocoa bean production (X3) on the dependent variable Indonesian cocoa bean export value (Y). This research uses a quantitative approach in the form of a time series. the data used is secondary data sourced from the Badan Pusat Statistik, Bank Indonesia, and the International Cocoa Organization starting from 2008 to 2022. The data analysis method is multiple linear regression (ordinary Least Square). Based on the results of the analysis obtained information that the price of cocoa beans has a significant impact on the export value of cocoa beans, the rupiah exchange rate has no affect the export value of cocoa beans, and cocoa bean production has a significant impact on the export value of Indonesian cocoa beans.